What security makes possible some thoughts on critical security studies - Burke, Anthony, 1966-; Australian National University. Department of International Relations (Canberra : Dept. of International Relations, Australian National University, 2007)
It has become commonplace to accept that security is a contested concept. How contested, however, seems to be what is at stake for critical approaches to security. With the U.S. Congress poised to ask for a National Intelligence Estimate on the security impacts of human-induced climate change, terrorism, people movements and disease the focus of national security policy, and various conceptualisations of human security informing national policy and new global norms, we are well into the broadening and deepening phase once seen as revolutionary. At the same time, state-centric discourses of security remain very powerful, and global patterns of insecurity, violence and conflict are getting more destructive and uncontrollable.
"June 2007".
Title from title screen (viewed on April 11, 2011)
Includes bibliographical references.
Text.
Mode of access: Internet via World Wide Web. Address as at 11/04/2011: http://ips.cap.anu.edu.au/ir/pubs/work_papers/07-1.pdf.
System requirements: Adobe Acrobat reader to access the document in PDF format.
Keywords: National security; Security, International; Climate change (Anthropogenic); Counter terrorist measures; National security; United States